2018
DOI: 10.1542/hpeds.2017-0167
|View full text |Cite
|
Sign up to set email alerts
|

Contraception for Adolescents and Young Adults in the Inpatient Setting: The Providers’ Perspective

Abstract: Initiation of a contraceptive method in the inpatient setting is acceptable to providers. In our findings, it is suggested that strategies are needed to enhance provision of these services by addressing confidentiality concerns and educating providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Youth recalled discussing options of birth control and receiving contraceptive counselling (Alexander et al, 2016; Donaldson et al, 2013; Hoopes et al, 2017; Marcell et al, 2010; Richards et al, 2016; Santelli et al, 2019; Snyder et al, 2016), including youth with latent tuberculosis (Hill et al, 2013), sickle cell disease (Nahata et al, 2018) and mobility limitations (Seburg et al, 2015). Likewise, HCPs reported providing anticipatory guidance about pregnancy prevention (Akers et al, 2010; Goldstein et al, 2018; Helitzer et al, 2011; Henry‐Reid et al, 2010; Marcell & Ellen, 2012; O'Sullivan et al, 2010). Among these articles, four provided details about the content of the conversations: HCPs noted that they discussed benefits and side effects of contraceptive methods (Akers et al, 2010; Marcell & Ellen, 2012); HCPs who specialized in male reproductive care prioritized discussion with male youth about female hormonal contraception and ways to support partners taking contraception (Marcell & Ellen, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Youth recalled discussing options of birth control and receiving contraceptive counselling (Alexander et al, 2016; Donaldson et al, 2013; Hoopes et al, 2017; Marcell et al, 2010; Richards et al, 2016; Santelli et al, 2019; Snyder et al, 2016), including youth with latent tuberculosis (Hill et al, 2013), sickle cell disease (Nahata et al, 2018) and mobility limitations (Seburg et al, 2015). Likewise, HCPs reported providing anticipatory guidance about pregnancy prevention (Akers et al, 2010; Goldstein et al, 2018; Helitzer et al, 2011; Henry‐Reid et al, 2010; Marcell & Ellen, 2012; O'Sullivan et al, 2010). Among these articles, four provided details about the content of the conversations: HCPs noted that they discussed benefits and side effects of contraceptive methods (Akers et al, 2010; Marcell & Ellen, 2012); HCPs who specialized in male reproductive care prioritized discussion with male youth about female hormonal contraception and ways to support partners taking contraception (Marcell & Ellen, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Youth noted that the power differential with an adult HCP prevented them from divulging sensitive information (Córdova et al, 2018; Hoopes et al, 2017). HCPs also reported feeling uncomfortable discussing sexuality due to cultural differences and religious reasons (Bray et al, 2010; Goldstein et al, 2018). When the subject of sexuality was broached, youth reported that they were able to recognize HCPs' discomfort and embarrassment in their use of vocal fillers, quick change of topics and lack of vocabulary precision in their conversations (Fuzzell et al, 2016; Hoopes et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pediatric hospital setting is uniquely equipped to address unmet reproductive care needs, given specific advantages such as prolonged providerepatient interactions across multiple days and the opportunity for confidential conversations when caregivers are not present. Previous studies show that although pediatric hospitalists agree that it is appropriate to provide reproductive services, most only infrequently offer safer sex counseling, condoms, or referral for contraception [18,30]. McFadden et al confirm that screening for sexual activity and unmet reproductive health needs does not routinely occur.…”
mentioning
confidence: 99%
“…The authors of "Contraception for Adolescents and Young Adults in the Inpatient Setting: The Providers' Perspective" contribute to the conversation on whether contraceptive services should be offered in the inpatient settings by offering the perspective of medical providers. This brief report by Goldstein et al 16 reveals an important finding: .80% of providers surveyed thought it would be appropriate to start a contraceptive for inpatients. Additionally, more than one-third of the respondents had already done so.…”
mentioning
confidence: 99%